A fractal analysis approach for predicting starch retrogradation from X‐ray diffractograms. Issue 1 (30th July 2013) - Utrilla‐Coello, Rubi G.; Bello‐Perez, Luis A.; Lara, Victor H.; Vernon‐Carter, Eduardo J.; Alvarez‐Ramirez, Jose; Tester, Richard F.
Abstract Commonly, the interpretation of starch XRD patterns is hampered by the lack of sharp intensity peaks and the presence of a broad background band. This work proposes a fractal analysis approach for the analysis of XRD patterns obtained from starches. The idea behind the fractal analysis approach is that the broad background pattern contains information pertaining the complexity of the material structure that presumably is arranged within fractal geometries. Thus, the quest is to detect regularities reflected as auto‐correlations of the complex intensity signal. The fractal rescaled range (R/S) analysis is proposed in this work to obtain an index for the regularity of the complex intensity signal. In turn, such regularity index should reflect the regularity of the complex starch structure. The approach is illustrated with native starches from maize, banana, and potato, showing that the former is more regular (i.e. more ordered starch structure) than the latter two. Gelatinization is used to contrast the fractal analysis results. In turn, it is shown that gelatinized starches exhibit a nearly amorphous structure reflected as non‐correlated XRD sequences.